Investigation of the chemical changes during the thermal treatment of acrylonitrile‐co‐methyl acrylate‐polymer (polyacrylonitrile‐precursor) focusing on the fate of the methyl acrylate moiety. Issue 18 (23rd December 2021) - Ruhland, Klaus; Horny, Robert; Wanzel, Andrea; Reisach, Sebastian; Nizamutdinova, Alina; Kirchhain, Holger; Rehfuss, Ulrich; van Wüllen, Leo; Fischer, Andreas; Scheliga, Felix; Hübner, Tobias
Abstract: Seventeen samples of acrylonitrile (AN)‐co‐methyl acrylate (MA)‐polymer (MA content 0–11 mol%) are examined. Several selective isotopic labelings are employed (d 1 ‐MA, d 2 ‐MA, 13 CO‐MA, CD3 ‐MA, d 1 ‐AN, d 2 ‐AN, and 15 N‐AN). The thermal treatment under inert atmosphere is investigated to gain insight into the chemical transformation mechanisms concerning the MA sub‐unit. The volatiles are determined by means of evolved gas analysis (EGA) (Fourier transform infrared [FTIR] and GC/MS). Methanol is found for the first time as one decisive volatile stemming from the MA sub‐unit, next to water and carbon dioxide. In addition, methylamines are proven to be formed by reaction of ammonia with the MA sub‐unit, while a similar reaction of hydrogen cyanide (HCN) yielding in acetonitrile could be ruled out. Several volatile compounds could even be quantified. The non‐volatile polymeric material is characterized by means of simultaneous thermal analysis (differential scanning calorimetry, thermogravimetric analysis), in‐situ‐FTIR spectroscopy and sophisticated solid‐state NMR methods. Selected defined model compounds are synthesized and analyzed for comparison. Detailed reaction mechanisms for the thermal transformation are concluded from the results, pointing in particular to the importance of ammonia for all processes as stoichiometric and/or catalytic reagent. Abstract : The fate of the methyl acrylate repeat unit in AN‐co‐MA‐polymers (polyacrylonitrile‐precursors for carbon fibers) on thermal treatment is studied in detail applying isotopic labeling of the starting material. Detailed reaction mechanisms are provided revealing that ammonia plays a key role in the reaction pathways and that the copolymer can be considered a smart thermally self‐switching material.